Do Emergency Medicine Residents Prefer Resident‐initiated or Attending‐initiated Feedback?. Issue 1 (January 2017) - McGhee, Jonathan; Crowe, Colleen; Kraut, Aaron; Pierce, Ava; Porat, Avital; Schnapp, Benjamin; Laurie, Amber; Fu, Rongwei; Yarris, Lalena
Abstract: Background: Real‐time feedback is crucial to improving physician performance. Emerging theory suggests that learner‐initiated feedback may be more effective in changing performance than attending‐initiated feedback, but little is known about how residents perceive resident‐ versus attending‐initiated feedback. Objectives: The primary aim was to determine whether residents' satisfaction varied by learner‐versus attending‐initiated feedback encounters. We hypothesized that residents would be more satisfied with resident‐initiated feedback. Methods: This was a multicenter study of five emergency medicine residency programs. We developed a milestones‐based, real‐time feedback intervention that provided behavioral anchors for ED subcompetencies and prompted a feedback discussion. The intervention was implemented at all sites for a 3‐month period from March to November 2014. Residents were asked to initiate one card per shift; attendings were also invited to initiate encounters and, in either instance, asked to provide one specific suggestion for improvement. Residents confidentially rated their satisfaction with feedback on a 10‐point scale. Reported satisfaction was categorized as "very satisfied" (score of 10) versus "less than very satisfied" (score < 10). Logistic regression was used to assess the difference in satisfaction between resident‐ versus attending‐initiated feedback, and random effects were used to account for the clustering of repeated ratings within resident and by site. Results: A total of 785 cards was collected from five sites. Participation varied by site (range = 21–487 cards per site). Of the 587 cards with both feedback initiator and satisfaction data, 67% (396/587) were resident‐initiated, and median satisfaction score was 10 (range = 4–10). There was no difference in the odds of being "very satisfied" by resident‐ vesus attending‐initiated encounters (odds ratio = 1.08, 95% confidence interval = 0.41 to 2.83). Conclusions: Our results suggest that residents are likely to be as satisfied with self‐initiated feedback as attending‐initiated feedback. Further research is needed to determine whether resident‐initiated feedback is more likely to be incorporated into practice and result in objective performance improvements.